A Foregut Cystic Neoplasm with Diagnostic and Therapeutic Similarities to Mucinous Cystic Neoplasms of the Pancreas - Kluger, Michael D; Tayar, Claude; Belli, Andrea; Salceda, Juan A; van Nhieu, Jeanne T; Luciani, Alain; Cherqui, Daniel (JOP. Journal of the Pancreas, 2013)
Context Greater utilization of cross-sectional abdominal imaging has increased the diagnostic frequency of cystic neoplasms of the pancreas. The “International Consensus Guidelines 2012 for the Management of IPMN and MCN of the Pancreas” illustrates a diagnostic and therapeutic algorithm for these lesions based on current knowledge. Case report We present a case of a 49-year-old woman with two years of intermittent epigastric pain found to have an 8.5 cm head of the pancreas mass on CT. Evaluation was consistent with a mucinous cystic neoplasm for which she underwent an uneventful pancreaticoduodenectomy. Histology revealed a bronchogenic cyst of the head of the pancreas. Discussion Bronchogenic cysts are congenital anomalies of the ventral foregut that can migrate into the abdomen prior to fusion of the diaphragm. They can easily be misdiagnosed for other benign and malignant retroperitoneal lesions. Similarly to mucinous cystic neoplasms, bronchogenic cysts have been reported to undergo malignant transformation. They can also become infected and hemorrhage. Therefore, resection should be performed in appropriate risk candidates. It is possible, with increased use of high resolution cross-sectional imaging, that these lesions may be identified with greater frequency in the abdomen and confused with other pancreatic neoplasms. The presence of ciliated respiratory epithelium and cartilage on pathology provides for definitive diagnosis. Image: Gross pancreaticoduodenectomy specimen.